Optimalisasi Gerakan Pemberdayaan dan Kesejahteraan Masyarakat Melalui Produk Mr. Brams Cookies Bawang Merah di Desa Klagen Kecamatan Rejoso - Nurul Mahruzah Yulia; Festian Cindarbumi (Institut Agama Islam Tribakti Kediri, 2023)
Shallots are the most potential agricultural product in Klagen Village, Rejoso District, Nganjuk Regency, East Java. Famous as a typical Indonesian spice, this typical Nganjuk Shallot has a different taste and texture from shallots in other regions. Unfortunately, even though this plant has potential and has many benefits for health and as a natural flavor enhancer, the people of Klagen village are not able to optimize and develop processed products from Shallots. With this service activity, the author aims to provide education to the public to increase the economic value of Shallots by processing them into Mr. Cookies. Brams. The service was carried out using the training method which was carried out with demonstrations and hands-on practice with several PKK mothers regarding how to process Mr. Cookies. Brams. In addition to processing, the training participants also gain knowledge for marketing a product. The results achieved from this service activity are the creation of processed innovations into Mr. Cookies. Brams, while adding to its economic value.